Evolution of government portals in India: mapping over stage models. Issue 4 (8th July 2014) - Tripathi, Rakhi; Gupta, M.P.
Abstract : Purpose: – The purpose of this paper is to assess whether the e-government stage models that have been developed in last one decade give a true indication of e-government growth in a developing country like India. Design/methodology/approach: – This exploratory study was conducted through a survey questionnaire from 300 portals of government departments and public sector undertakings (PSUs) in India. Findings: – Results show that on e-government stage model; only 28 per cent of the surveyed government department have achieved the transactional stage whereas 58 per cent have reached at least a minimum level of vertical integration. On the other hand, 74 per cent PSUs are at transactional level and 69 per cent have achieved at least a minimum level of vertical integration. Practical implications: – For achieving a one-stop government portal, integration stage can be achieved before the transaction level. Reason behind this being nature and requirement of the portal. There are fundamental differences in social and political factors of various countries that demand more customized local models. Originality/value: – This study is the first to examine the evolution of government portals in India. The results lead to a number of insights such as there are few government portals that do not follow the proposed stage models and achieve the integration level before attaining the transaction level.